Proactive enrollment of parents to tobacco quitlines in pediatric practices is associated with greater quitline use: a cross-sectional study. (December 2016) - Drehmer, Jeremy; Hipple, Bethany; Nabi-Burza, Emara; Ossip, Deborah; Chang, Yuchiao; Rigotti, Nancy; Winickoff, Jonathan
Abstract Background Every U.S. state has a free telephone quitline that tobacco users can access to receive cessation assistance, yet referral rates for parents in the pediatric setting remain low. This study evaluates, within pediatric offices, the impact of proactive enrollment of parents to quitlines compared to provider suggestion to use the quitline and identifies other factors associated with parental quitline use. Methods As part of a cluster randomized controlled trial (Clinical Effort Against Secondhand Smoke Exposure), research assistants completed post-visit exit interviews with parents in 20 practices in 16 states. Parents' quitline use was assessed at a 12-month follow-up interview. A multivariable analysis was conducted for quitline use at 12 months using a logistic regression model with generalized estimating equations to account for provider clustering. Self-reported cessation rates were also compared among quitline users based on the type of referral they received at their child's doctor's office. Results Of the 1980 parents enrolled in the study, 1355 (68 %) completed a 12-month telephone interview and of those 139 (10 %) reported talking with a quitline (15 % intervention versus 6 % control;p < .0001). Parents who were Hispanic (aOR 2.12 (1.22, 3.70)), black (aOR 1.57 (1.14, 2.16)), planned to quit smoking in the next 30 days (aOR 2.32 (1.47, 3.64)), and had attended an intervention practice (aOR 2.37 (1.31, 4.29)) were more likely to have talked with a quitline. Parents who only received a suggestion from a healthcare provider to use the quitline (aOR 0.45 (0.23, 0.90)) and those who were not enrolled and did not receive a suggestion (aOR 0.33 (0.17, 0.64)) were less likely to talk with a quitline than those who were enrolled in the quitline during the baseline visit. Self-reported cessation rates among quitline users were similar regardless of being proactively enrolled (19 %), receiving only a suggestion (25 %), or receiving neither a suggestion nor an enrollment (17 %) during a visit (p = 0.47). Conclusions These results highlight the enhanced clinical effectiveness of not just recommending the quitline to parents but also offering them enrollment in the quitline at the time of their child's visit to the pediatric office. Trial registration ClinicalTrials.gov, Identifier:NCT00664261